Penerapan Buerger Allen Exercise Terhadap Nilai Sensitivitas Kaki Pada Klien Dengan Diabetes Melitus Tipe 2: Penerapan Buerger Allen Exercise Terhadap Nilai Sensitivitas Kaki Pada Klien Dengan Diabetes Melitus Tipe 2 - Asih Minarningtyas Naning; Muftadi Muftadi (FKF, 2024)
Background : Interventions that can be done to accelerate vascularizationand increase sensitivity of foot on diabetes melitus patient is doing thebuerger allen exercise. Buerger allen exercise is a form of activemovement in the plantar area by applying a gradual gravitational.Monofilament test is a tool that used to assess the sensitivity of foot. Purpose: this case study aims to know the real picture of Buerger allenexercise on the value of foot sensitivity with the nursing process approach.Methodology: The design that we used is a case study by using analyticaldescriptive method through data collection techniques such as observationand documentation. Result: The Implementation showed that before andafter doing the buerger allen exercise for 6 days, there is an increase onfoot sensitivity to clients who suffer type 2 of diabetes melitus.Recommendation: For patients with type 2 diabetes melitus, can dobuerger allen exercise independently to increase the sensitivity value ofthe foot.